SINDIRAN DALAM WAYANG DURANGPO - Wahyuni, Lucia Indah Dwi; Kulup, Luluk Isani (Buana Pendidikan, 2013)
Language generally appears in the linguistic and non-linguistic social process. Language always comes in the form of text, because language in text form is always the realization of a verbal, whether it be central or dominant as in the linguistic and social process that are peripheral or that complements the non-linguistic processes. Language in the form of text always brings social functions of a social process in a society. As well as this Durangpo Puppet discourse that tells about the social life and political disputes. In the story the author reveals more use of stylistic allusions and figures used in the story is to use the puppet characters. So interesting to be observised if Discourse Puppet Durangpo analyzed in terms of form and meaning of satire. The base of the theory used in this study is the theory of satire which consists of three kinds of irony, cynicism and sarcasm. The method used in this research is descriptive qualitative approach. Because this study describes the results of research through words. Data collected in the form of text containing Durangpo discourse Puppet satire. Data collection is done by reading the text and notes. From reading research techniques to collect data, which are words or phrases that contain allusions are then grouped and coded data. The data has been further interpreted in the form of exposure dieksplanasi language as a result of an analysis. The results obtained from this study is the insinuation in Puppet Durangpo to know the shape and meaning of satire contained in Puppet Durangpo discourse. Meaning contained in the discourse lead to more Durangpo Puppet social and political criticism.